2017
DOI: 10.1002/lary.26581
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension: Contemporary review and implications for the otolaryngologist

Abstract: Objectives: 1) Review controversies pertaining to the pathophysiology, diagnosis, and treatment of idiopathic intracranial hypertension. 2) Discuss the evolving role of otolaryngologists in managing this disease and related disorders.Data Sources: Primary literature review, Centers for Disease Control and Prevention website, International Classification of Headache Disorders, Second Edition.Methods: A comprehensive review of the primary literature was performed from 1990 to 2016 utilizing keywords idiopathic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 113 publications
(372 reference statements)
2
52
0
Order By: Relevance
“…6 Classical clinical signs of IIH include headache and visual symptoms, such as transient obscurations, tinnitus, papilledema, and diplopia. 16 Yet most patients had only headaches as the leak likely provided a release valve of the increased ICP. An empty sella was the most common concurrent MRI finding, suggesting history of underlying increased ICP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Classical clinical signs of IIH include headache and visual symptoms, such as transient obscurations, tinnitus, papilledema, and diplopia. 16 Yet most patients had only headaches as the leak likely provided a release valve of the increased ICP. An empty sella was the most common concurrent MRI finding, suggesting history of underlying increased ICP.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some association does exist between IIH, lateral, and anterior skull base CSF leaks. 16 Recent studies have raised the possibility of obstructive sleep apnea as a risk factor for spontaneous CSF leaks. In a meta-analysis of three studies, patients with spontaneous CSF leaks were 2.85 times more likely than those with nonspontaneous CSF leaks to have obstructive sleep apnea (OSA).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Banks etal.’s retrospective review demonstrated that BMI was statistically significantly higher in spontaneous CSF leaks compared to other CSF leak etiologies. Several authors note the concurrent increase of spontaneous CSF leaks (as well as IIH) in conjunction with the increasing obesity epidemic, although it is unclear if this could be increasing recognition and diagnosis of spontaneous CSF leaks …”
Section: Primary Csf Rhinorrheamentioning
confidence: 99%
“…CSF production and its ow characteristics serve as a key component of the physiological homeostasis, immunological protection, and metabolic maintenance of the central nervous system. Perturbations of CSF homeostasis can result in pathological outcomes such as idiopathic intracranial hypertension (IIH), which often results in headaches and ocular pathologies [1,2]. Magnetic resonance imaging (MRI) studies in astronauts before and after space ight missions have shown perturbations to the CSF spaces, predominantly after long-duration missions, including narrowing of the central sulcus, upward shift of the brain, and narrowing of the CSF spaces at the vertex [3].…”
Section: Introductionmentioning
confidence: 99%